Non-invasive Vagus Nerve Stimulation in Cerebral Stroke: Current Status and Future Perspectives - Li, Lijuan; Wang, Dong; Pan, Hongxia; Huang, Liyi; Sun, Xin; He, Chengqi; Wei, Quan (Frontiers in Neuroscience, 2022)
Stroke poses a serious threat to human health and burdens both society and the healthcare system. Standard rehabilitative therapies may not be effective in improving functions after stroke, so alternative strategies are needed. The FDA has approved vagus nerve stimulation (VNS) for the treatment of epilepsy, migraines, and depression. Recent studies have demonstrated that VNS can facilitate the benefits of rehabilitation interventions. VNS coupled with upper limb rehabilitation enhances the recovery of upper limb function in patients with chronic stroke. However, its invasive nature limits its clinical application. Researchers have developed a non-invasive method to stimulate the vagus nerve (non-invasive vagus nerve stimulation, nVNS). It has been suggested that nVNS coupled with rehabilitation could be a promising alternative for improving muscle function in chronic stroke patients.In this article, we review the current researches in preclinical and clinical studies as well as the potential applications of nVNS in stroke. We summarize the parameters, advantages, potential mechanisms, and adverse effects of current nVNS applications, as well as the future challenges and directions for nVNS in cerebral stroke treatment. These studies indicate that nVNS has promising efficacy in reducing stroke volume and attenuating neurological deficits in ischemic stroke models. While more basic and clinical research is required to fully understand its mechanisms of efficacy, especially Phase III trials with a large number of patients, these data suggest that nVNS can be applied easily not only as a possible secondary prophylactic treatment in chronic cerebral stroke, but also as a promising adjunctive treatment in acute cerebral stroke in the near future.